PENGARUH MODAL USAHA DAN LAMA USAHA TERHADAP PENDAPATAN USAHA (STUDI PADA PELAKU EKONOMI KREATIF SUB SEKTOR FASHION DI KOTA MALANG) - Elly Ernawati; Jeni Susyanti; Muhammad Agus Salim (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to examine whether the influence of venture capital and business duration on business income in creative economic actors in the fashion sub-sector in Malang City. The variables used by researchers are venture capital and business duration (dependent variable) and business income (independent variables) this study uses a quantitative approach. Sampling uses a saturated sample method. There are 43 business actors that meet the sample category. Furthermore, multiple regression analysis is used to analyze and test hypotheses with the t test with the help of SPSS version 14. Based on the results of the study indicate that business capital affects income. And the length of business has an effect on income. This explains that businesses can manage finances well and are able to maintain their business so they can increase income. Keywords: Business Capital, Duration of business, Operating Income.